FREQUENCY OF MULTI-DRUG RESISTANT (MDR) AND EXTENDED DRUG RESISTANT (XDR) SALMONELLA TYPHI IN PATIENTS PRESENTING WITH CULTURE PROVEN ENTERIC FEVER AT TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Objectives: To determine frequency of multi-drug and extended drug resistance Salmonella typhi in patients presenting with culture proven enteric fever and its distribution based on age, gender and duration of typhoid fever.Study Design: Prospective descriptive study.Place and Duration of Study: Department of Medicine, Pakistan Institute of Medical Sciences, Islamabad from 01/10/2024 to 31/03/2025.Methodology: A total of 202 culture proven cases of enteric fever were included. Baseline characteristics including age, gender and duration of fever were documented. In all these patients, subcultures will be sent to determine antibiotic sensitivity pattern of the Salmonella strains. Based on results of culture and sensitivity, multi-drug resistant and extended drug-resistant strains were identified.Results: In present study, there were 78 (78.00%) males and 22 (22.00%) females. Mean duration of enteric fever was 5.31 ± 1.94 days. Frequency of multi-drug and extended drug-resistant strains of Salmonella typhi was 37 (18.32%) and 88 (43.56%), respectively.Conclusion: Frequency of multi-drug and extensively drug-resistant strains of Salmonella typhi is quite high in target population of present study.